Diversity of Forensic Cases at Abdoel Wahab Sjahranie Regional Hospital for the period January 2021-December 2022 Keragaman Kasus Forensik di RSUD Abdoel Wahab Sjahranie periode Januari 2021-Desember 2022: Diversity of Forensic Cases at Abdoel Wahab Sjahranie Regional Hospital, January 2021-December 2022 - Tololiu, Ayub Agus; Nugroho, Hary; Danial (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
Forensics is a scientific field that uses science or expertise to aid in the process of law enforcement. The purpose of this study is to determine variety of forensic cases found at Abdoel Wahab Sjahranie Hospital from January 2021 to December 2022. This is a descriptive retrospective study that was carried out in February 2023. The Visum et Repertum sheet was used to collect data from 254 living and deceased victims at Abdoel Wahab Sjahranie Hospital's Forensic Installation. According to the findings, the most common case among living victims was injury, whereas blunt violence was the leading cause of death. While most of the deceased victims were men, the majority of the living victims were women. The age range of 20 to 60 was the most prevalent for both live and deceased victims. While working was the most common occupation for deceased victims, students were the most common occupation for those who were still alive. The most typical type of inspection performed on deceased victims was an external examination. Keywords: Forensic cases, Abdoel Wahab Sjahranie Regional Public Hospital